Microfinance evolution, achievements and challenges (London ITDG, 2003)
Selected by Malcolm Harper, this compilation comprises fourteen articles on the major developments in microfinance in the last twelve years. Some show how certain aspects of the field have changed quite dramatically, others cover issues which have continued throughout the period to preoccupy practitioners and policy makers, and others raise critical and worrying concerns about the future of microfinance. All have been written by experienced authorities, with practical experience, and several are widely regarded as seminal contributions. The reader will be useful for students and others who are looking for a wide-ranging introduction to microfinance, for national and international policy makers and donors, and for people who work in the field and are looking for a broad overview of trends and alternative strategies. Includes an introduction by Malcolm Harper, founding editor of the journal "Small Enterprise Development".
Includes bibliographical references.
Keywords: Microfinance